PENYELESAIAN DEBITUR WANPRESTASI DALAM PERJANJIAN KREDIT JAMINAN FIDUSIA MENURUT UNDANG-UNDANG NO. 42 TAHUN 1999 TENTANG JAMINAN FIDUSIA - Asuan, Asuan (Faculty of Law, University of Palembang, 2018)
Type of research in doctrinal law or better known as normative legal research which is also called normative juridical (legal research) concerning the legal issues at hand. The approach to the law (statue approach) is carried out by examining the laws and regulations. In writing with primary and secondary data obtained from library materials namely Law No. 42 of 1999 concerning Fiduciary Guarantees, Law No. 10 of 1998 concerning Banking, Government Regulations, Civil Code, KUH Trade and literature, lecture materials and other sources related to credit agreements with fiduciary guarantees and problems in particular. In granting credit with fiduciary guarantees through the stages of the procedure for credit application and the making of a fiduciary deed at the notary who is registered with the Office of Fiduciary Registration to provide legal certainty for creditors (banks). Credit settlement process if the debtor is malicious, the bank is based on a substitution power of attorney from the debtor made a notariil Fiduciary deed and registered with the Fiduciary Office, the debtor makes a sale under the hands, the sale of collateral is voluntary, the result is submitted to the bank to repay the loan, the bank can conduct the auction in general and through the Court.